Towards an understanding of land consumption in Germany – outline of influential factors as a basis for multidimensional analyses - Kretschmer, Odette; Ultsch, Alfred; Behnisch, Martin (ERDKUNDE, 2015)
Like many other industrialized countries, Germany is affected by the continuing conversion of open space into settlements and transportation infrastructure. Between 2000 and 2010 the rate of conversion was about 12 m² per second. In order to ensure an ecologically-oriented urban and regional development, it is vital to manage land responsibly as a finite resource. Against this background, the topic of sustainable land management is the focus of various fields of spatial research and spatial policy discussion. The current article documents the systematic building of knowledge on factors linked to the expansion of settlements and transportation infrastructure. The selection of so called influential factors presented here is based on a comprehensive literature review as well as expert interviews. The paper aims to support future studies in the selection and verification of variables to be applied to multidimensional analyses of influential factors (e.g. statistical and data mining methods). Such studies are currently still at an early stage both in Germany and other central European nations.